Optimizing Algebraic Thinking in Elementary Students: Exploring the Impact of Generative Learning - Evi , Evi; Yurniwati, Yurniwati; Ulfa, Maria; Budiono (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2024)
This research aims to optimize algebraic thinking in elementary school students through the application of a generative learning model. The research approach uses an experimental method with a post-test-only design. The research was conducted on grade V students of SD Negeri Kalisari 03, which consisted of 64 students from two classes which were then divided into 2 groups, namely the experimental class and the control class. Data analysis was carried out with descriptive and inferential statistics, with the help of SPSS, first a prerequisite test was carried out, namely a normality test and a homogeneity test, and the hypothesis of this research was carried out using the two-track variance analysis (ANOVA) method. The results of the study showed an increase by obtaining a significance value of less than 0.05 with a mean square of 476,190. This means that the KBA of students who learn using the Generative model is better compared to students who learn using the Expository model. The application of the generative learning model can improve students' algebraic thinking skills in two indicators of algebraic thinking ability, namely: generalizing the arithmetic pattern of a problem and understanding mathematical modeling from the four indicators used in this study.